Effects of Prophylactic Lipofilling After Radiotherapy Compared to Non–Fat Injected Breasts: A Randomized, Objective Study. (29th June 2020) - Gentilucci, Marika; Mazzocchi, Marco; Alfano, Carmine
Abstract: Background: Patients who are suffering from invasive breast cancer may require post-mastectomy radiation therapy (PMRT). PMRT improves outcomes in breast cancer patients in terms of locoregional recurrence. Preliminary studies indicate that fat injections reduce post-radiation damage of soft tissue and implants. Objectives: The aim of this study was to demonstrate the safety and effectiveness of prophylactic fat injections on radiated implanted breasts. Methods: The authors randomly assigned 60 female patients to either Group A or B. Group A patients received 3 breast fat injections, according to Coleman's technique, after radiotherapy and before expander removal with definitive implant insertion. Group B patients underwent surgery without lipofilling. At each surgical operation, skin biopsies were performed in a specific breast area to evaluate adipose tissue thickness, and a statistical analysis of the thickness variations was performed with the Wilcoxon's sum test. Disability was assessed according to the Late Effects of Normal Tissues-Subjective Objective Management Analytic scale. Results: The study demonstrates a qualitative and quantitative improvement about tissues after fat injection. This is highlighted by the significant increase in thickness after lipofilling. Conclusions: The study, which is based on both clinical and histological findings and is supported by the comparison of a control group with a 1-year follow-up, demonstrates that fat injections reduce tissue radio damage, improving reconstructive surgery outcomes and quality of life. Level of Evidence: 2: